Auxiliary Screening COVID-19 by Serology - Xiongfeng Pan; Atipatsa C. Kaminga; Atipatsa C. Kaminga; Yuyao Chen; Hongying Liu; Shi Wu Wen; Shi Wu Wen; Shi Wu Wen; Yingjing Fang; Peng Jia; Peng Jia; Aizhong Liu (Frontiers Media S.A., 2022)
BackgroundThe 2019 novel coronavirus (COVID-19) pandemic remains rampant in many countries/regions. Improving the positive detection rate of COVID-19 infection is an important measure for control and prevention of this pandemic. This meta-analysis aims to systematically summarize the current characteristics of the auxiliary screening methods by serology for COVID-19 infection in real world.MethodsWeb of Science, Cochrane Library, Embase, PubMed, CNKI, and Wangfang databases were searched for relevant articles published prior to May 1st, 2022. Data on specificity, sensitivity, positive/negative likelihood ratio, area under curve (AUC), and diagnostic odds ratio (dOR) were calculated purposefully.ResultsSixty-two studies were included with 35,775 participants in the meta-analysis. Among these studies, the pooled estimates for area under the summary receiver operator characteristic of IgG and IgM to predicting COVID-19 diagnosis were 0.974 and 0.928, respectively. The IgG dOR was 209.78 (95% CI: 106.12 to 414.67). The IgM dOR was 78.17 (95% CI: 36.76 to 166.25).ConclusionOur findings support serum-specific antibody detection may be the main auxiliary screening methods for COVID-19 infection in real world.